Qualitative and quantitative analysis of diosmin content of hyssop (Hyssopus officinalis) in response to salinity stress. Issue 10 (October 2021) - Soheilikhah, Zhaleh; Modarresi, Masoud; Karimi, Naser; Movafeghi, Ali
Abstract: Hyssop ( Hyssopus officinalis L.) is a perennial subshrub, which is distributed across the eastern Mediterranean region to central Asia. One of the most important bioactive compounds of hyssop is diosmin, a flavone glycoside of diosmetin, with application in the field of cardiovascular therapy. Salinity as one of the most essential environmental stress factors is able to alter secondary metabolite content in plants. Therefore, we aimed to investigate the effect of salinity on the levels of total flavonoid content and diosmin in hyssop. Accordingly, salinity stress was imposed by watering plants with four different concentrations of sodium chloride (NaCl) (50, 100, 150 and 200 mM) for 4 weeks. High-performance liquid chromatography (HPLC) method was used for purification of diosmin from dried leaves and measurement of it in dried shoots. Nuclear magnetic resonance (NMR) spectroscopy was applied for determination of the structure of diosmin. The obtained results showed that high salinity levels lead to a higher amount of total flavonoid and diosmin content in treated plants. Although alteration in diosmin content was not significant in treatments up to 100 mM NaCl, higher amounts of diosmin were observed in 150 and 200 mM NaCl salinity levels. We concluded that the contents of total flavonoid and diosmin were significantly elevated after exposure of hyssop plants to salt stress conditions. Abstract : Diosmin; Flavonoid; HPLC; Hyssop; Salinity stress.